2015
DOI: 10.3233/bmr-140537
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality in patients with chronic low back pain: A cross-sectional study assesing its relations with pain, functional status and quality of life

Abstract: The sleep quality of patients with CLBP was worse compared to HCs, and there were positive relations between the sleep quality with pain and functional status. Also, the poor sleep quality had negative effect on the physical component of quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 0 publications
5
38
1
1
Order By: Relevance
“…However, improvements during the study period in LBP and disability were indeed associated with improvement in sleep quality, which may suggest that pain, disability and sleep quality may be influenced by common factors (Alsaadi et al., ; Aili et al., ). This would explain results from this study as well as previous reports on associations between pain and sleep quality in patients with LBP (Alsaadi et al., , , ; Kelly et al., ; Ropponen et al., ; Aili et al., ; Sezgin et al., ), and differences in self‐reported sleep quality across healthy controls and patients with LBP (Marty et al., ; O'Donoghue et al., ; van de Water et al., ; Sezgin et al., ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, improvements during the study period in LBP and disability were indeed associated with improvement in sleep quality, which may suggest that pain, disability and sleep quality may be influenced by common factors (Alsaadi et al., ; Aili et al., ). This would explain results from this study as well as previous reports on associations between pain and sleep quality in patients with LBP (Alsaadi et al., , , ; Kelly et al., ; Ropponen et al., ; Aili et al., ; Sezgin et al., ), and differences in self‐reported sleep quality across healthy controls and patients with LBP (Marty et al., ; O'Donoghue et al., ; van de Water et al., ; Sezgin et al., ).…”
Section: Discussionsupporting
confidence: 81%
“…Approximately 55-60% of patients with LBP report impaired sleep after pain onset (Marin et al, 2006;Alsaadi et al, 2011), and over half suffer from insomnia (Tang et al, 2007). Several studies have suggested that there is correlation between poor sleep quality and low back pain (Kaila-Kangas et al, 2006;Marty et al, 2008;O'Donoghue et al, 2009;Auvinen et al, 2010;Kelly et al, 2011;van de Water et al, 2011;Alsaadi et al, 2013Alsaadi et al, , 2014Ropponen et al, 2013;Aili et al, 2015;Sezgin et al, 2015). Insufficient sleep quantity or quality has also been suggested to be a risk factor for neck and LBP among girls (Auvinen et al, 2010), and for being hospitalized for LBP among industrial employees (van de Water et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Severe chronic pain may have sequelae such as the avoidance of physical activity and sleep loss. An unfortunate cascade can then develop, leading to deconditioning, disability, work absence (6), decreases in participation, mood changes, and overall lower quality of life (5,(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…For people with chronic OA or spinal pain, these persistent symptoms of poor sleep habits, irregular sleep scheduling, and fear of not sleeping, can develop into chronic insomnia which does not necessarily resolve from the reduction of pain alone 19 . Chronic insomnia further complicates management for people with OA and spinal pain, being associated with more severe pain presentation 15,20 , presence of depression 21,22 , and poorer physical function 23,24 . This is likely due to the bidirectional relationship between sleep and pain 25 , meaning that poorer sleep may lead to worse pain, and worse pain may lead to poorer sleep.…”
Section: Introductionmentioning
confidence: 99%